Literature as a function of aristotelian “catharsis”: a study in relation to shame by salman rushdie - Anandawansa, B.D.K. (University of Jaffna, 2012)
The Greek term “Catharsis” has two principle meanings: purgation and purification. More specifically, the crux between the two meanings holds the notion of “Catharsis” as a medical purgation of excessive emotions on one hand, and the ceremonial purification of the “body” on the other. In more liberal terms, purgation of emotions deals with the physical or non moral, while the moralistic element of purification of the soul comes in the other. Aristotle’s notion of “Catharsis” was extensively applied to poetry and tragedy, and explored the effects of how spectators’ emotions such as pity and fear are cleansed through characters on stage. The argument of this paper is that the body of Literature, as a whole, is a matrix in which both the writers and the readers or spectators, relentlessly purge their emotions and purify their souls. In other words, the act of generating a poem, writing a novel or a piece of drama is a metaphor used by the authors, wherein writers dress characters to vent their views, emotions, likes and dislikes. Alternatively, this production purifies their souls. For the reader or the spectator, Literature is more close to the original sense of the word “Catharsis” mentioned on the onset. The aim of this paper is to explore the notion of “Catharsis” providing examples from a selected work of literature, namely Salman Rushdie’s Shame.